The cost of the Ukraine War for Russia prepared for the Department of the Air Force - Shatz, Howard J. 1960- (RAND, 2023)
In this report, RAND researchers present estimates of what costs Russia is incurring as a result of its invasion of Ukraine. As of September 2022, researchers estimated military costs reached $40 billion. Full-year 2022 gross domestic product losses amounted to between $81 billion and $104 billion and full-year financial capital destruction reached $322 billion. Direct military spending may amount to almost $132 billion through 2024. Over the long term, even with a stalemated war, Russia's economy and the standard of living of its people are likely to decline. The main factor sustaining Russia's economy is the export revenue it earns from oil and gas sales. Despite these significant economic losses, RAND researchers judged these costs to be sustainable for the next several years
Title from PDF document (title page; viewed December 19, 2023)
"RAND PROJECT AIR FORCE
"Prepared for the Department of the Air Force
Keywords: Geschichte 2022-2023; Russisch-Ukrainischer Krieg; Kosten; Russland; Russian Invasion of Ukraine, 2022 / Costs; Armed Forces / Appropriations and expenditures; Budget / Russia (Federation); Russian Invasion of Ukraine, 2022 / Economic aspects; Russia (Federation) / Economic conditions / 21st century; Russia (Federation) / Economic policy / 21st century; Russia (Federation) / Foreign economic relations / 21st century; International Economic Relations; Military Budgets and Defense Spending; Russia; Ukraine; Warfare and Military Operations; Forces armées / Crédits budgétaires et dépenses; Budget / Russie